Criminal Investigative Analysis by Gregg O. McCrary - McCrary, Gregg O. (1999)
Retired FBI Special Agent Gregg O. McCrary was asked by the State to analyze the crime and crime scene and review all pertinent case materials in order to classify this homicide. He was asked to offer opinions regarding victimology, motive and the likelihood of more than one offender being involved in this crime. McCrary concluded that the crime most resembled a staged domestic homicide as defined in the Crime Classification Manual. Some of the reasons for this classification included: inappropriate items were taken from the crime scene to make it appear as if burglary was the motive; no clear point of entry by the murderer was determined; there was excessive trauma beyond which was necessary to cause death; the murder weapon, fingerprints and other evidence were removed and the offender positioned the victim to infer that sexual assault had occurred, but it had not